Commodification of Identity in Local Political Contests on Instagram: Komodifikasi Identitas Pada Kontestasi Politik Lokal di Instagram - Amalia, Fara Putri; Dharma, Ferry Adhi (Universitas Muhammadiyah Sidoarjo, 2025)
Identity politics, such as ethnicity, religion, and local traditions, are often exploited to win political competition. Social media platforms like Instagram have become strategic media for building image and mobilizing support through visual content. This study examines the construction of political hyperreality by two official mayoral candidate accounts, namely @achmadamiraslichin and @cakband1, on the Instagram platform using Baudrillard's Simulacra and Simulation theory approach. By packaging visual posts, this couple creates a